Feature extraction from step AP224 file sets - Azmi, Azwan Iskandar; Mohd. Taib, Jamaludin; Muhammad, Zulkepli (Faculty of Mechanical Engineering, 2003)
Feature technology transforms the low-level geometrical definition of a 3D model into high level product definition, aiming for full automation of downstream manufacturing activities. Today, feature has been implemented in Standard for Exchange of Product Model specifically in Application Protocol 224 (STEP AP224) which utilizes manufacturing feature definition based on prismatic and turning parts. Hence, this research is carried out to study how STEP AP data is stored and how the features can be extracted. The extracted features are then used to automate the generation of the NC Code for the milling process. This work is limited to isolated milling features on 2.5D parts or prismatic parts.